2018
DOI: 10.1136/tobaccocontrol-2018-054268
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking among those with mental disorders in the US population: 2012–2013 update

Abstract: BackgroundRecent nationally representative estimates from the USA suggest the prevalence of cigarette smoking continues to be much higher among those with mental disorders compared with those without; however, prevalence estimates for current cigarette use by specific diagnoses are outdated.MethodsWe analysed data from the National Epidemiologic Survey on Alcohol and Related Conditions III (2012–2013). We estimated the prevalence of lifetime and past-year smoking, lifetime and past-year daily smoking, and life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 46 publications
2
31
1
1
Order By: Relevance
“…Among those with a common mental health disorder in England, smoking prevalence remains around 50% higher [4] and this increases further for more severe mental disorders [5]. Figures for the US similarly show an increased burden of smoking among those with mental health problems [6,7]. The relationship is complex but appears to be bidirectional [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Among those with a common mental health disorder in England, smoking prevalence remains around 50% higher [4] and this increases further for more severe mental disorders [5]. Figures for the US similarly show an increased burden of smoking among those with mental health problems [6,7]. The relationship is complex but appears to be bidirectional [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Among those with a common mental health disorder in England, smoking prevalence remains around 50% higher [5], and this increases further for more severe mental disorders [6]. Figures for the US also show an increased burden of smoking among those with mental health problems [7][8][9]. About one third of smokers have a mental health problem [6,10], and the relationship between mental health and smoking is complex and appears to be bidirectional [4,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Smith PH, et al found a high prevalence of smoking among patients with depression, general anxiety disorders, and mental disorders. They found that smoking is more common among individuals with mood, anxiety, and substance use disorders, with the highest rates among those with bipolar and substance use disorders [17]. To note the important function of BDNF in the nervous system, we decided to evaluate the epigenetic changes of the BDNF gene in the smokers' individuals.…”
Section: Introductionmentioning
confidence: 99%